2005
DOI: 10.1111/j.1365-2222.2005.02201.x
|View full text |Cite
|
Sign up to set email alerts
|

Why generic and disease‐specific quality‐of‐life instruments should be used together for the evaluation of patients with persistent allergic rhinitis

Abstract: The SF-36 and RQLQ are good for discriminating rhinitis patients from controls, but the former is poor for detecting changes in QOL. Both are inappropriate for mildly symptomatic patients. Each instrument measures non-overlapping halves of the measurable HRQL. For an assessment of the HRQL in persistent AR that is complete and responsive both instruments should be employed together.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 43 publications
(57 reference statements)
1
25
0
1
Order By: Relevance
“…This pattern of findings is consistent with previous research suggesting that condition-specific HRQL measures tend to be more responsive than generic HRQL measures [34][35][36]. For example, a comparison of generic to condition-specific measures across 43 randomized clinical trials found that the condition-specific measures were more responsive to change, particularly in studies with a nonzero therapeutic effect [34].…”
Section: Discussionsupporting
confidence: 90%
“…This pattern of findings is consistent with previous research suggesting that condition-specific HRQL measures tend to be more responsive than generic HRQL measures [34][35][36]. For example, a comparison of generic to condition-specific measures across 43 randomized clinical trials found that the condition-specific measures were more responsive to change, particularly in studies with a nonzero therapeutic effect [34].…”
Section: Discussionsupporting
confidence: 90%
“…The participants were instructed according to the guidelines defined by the designers of the questionnaires. As proposed by several authors, we used a combination of generic and disease specific quality of life scales (Leong et al 2005; Terreehorst et al 2004). The study participants were asked if any serious or dramatic event had happened during the observation period to exclude response shift (van Gerth Wijk 2002).…”
Section: Methodsmentioning
confidence: 99%
“…The overall RQLQ score is the mean of all 28 responses and the individual domain scores are the means of the items in those domains. The RQLQ has been adapted to many different cultures and languages [Bunnag et al 2005;Okuda et al 2005;Nascimento Silva et al 2001;Leong et al 1999]. Also, the RQLQ has been tested in adult patients with seasonal, perennial as well as intermittent and persistent AR [Juniper and Guyatt, 1991].…”
Section: Specific Questionnairesmentioning
confidence: 99%